Association analysis for yield and component traits in sunflower (Helianthus annuus L.): ASSOCIATION ANALYSIS FOR YIELD AND COMPONENT TRAITS IN SUNFLOWER - REENA RANI; R K SHEORAN; SUBHASH CHANDER (Journal of Oilseeds Research, 2016)
Ninety genotypes of sunflower were evaluated for the estimation of correlation and path analysis. Data were recorded for yield and its component traits viz., days to 50% flowering, days to maturity, duration of reproductive phase, plant height, stem girth, head diameter, 100-seed weight, seed filling percentage, hull content (%), protein content (%), oil content (%) and seed yield per plant (g). The seed yield per plant showed positive and significant correlation with seed filling percentage, head diameter, oil content and 100-seed weight showed negative correlation with days to 50% flowering, days to maturity and hull content. This shows that head diameter, 100-seed weight, seed filling percentage and oil content are the major yield contributing traits to be given more selection pressure for improving yield. The path coefficient analysis showed that 100-seed weight had the highest direct and positive effect on seed yield per plant followed by head diameter, plant height and oil content had positive direct effects on seed yield. So, direct selection of genotypes for seed yield through these traits may be effective.